Biochar from pyrolysis of cellulose: An alternative catalyst support for the electro-oxidation of methanol - Nieva Lobos, María Luz (2016)
In the present study, the biochar produced by fast pyrolysis at 350 C of untreated and acid treated cellulose are evaluated as supports of CueRu@Pt core-shell nanoparticles (2.9 e3.5 nm) for the electro-oxidation of methanol in acid media. Carbon materials and the supported core-shell nanoparticles were characterized by physicochemical and electrochemical techniques. Cyclic voltammetry and chronoamperometry were used to study the activity of the catalysts. The nanocatalyst supported onto the biochar from acid-treatedcellulose exhibited high electroactive surface area (38 m2/g) and high performance in the methanol electro-oxidation reaction, reaching TON values of 0.151 molec. (sites s)1 at 0.5 V. This contribution provides a new approach for the utilization of an inexpensivecarbon material precursor as cellulose to design alternative catalytic systems and their emerging applications in electrocatalysis.